La “Stiva da Morts”. In bilico tra due dimensioni sensoriali - Valerio Botta (ArchAlp, 2024)
In Vrin there is a building that is not dissimilar frommost of the buildings in the village in terms of its general characteristics, but at the same time it appears as an autonomous element in relation to its context. This building is known as ‘Stiva da Morts’, chamber of the dead, by the villagers, and was designed by architect Gion A. Caminada to host the traditional ritual of visiting the deceaseed in their coffin before burial. This ritual took on collective meanings in addition to the sentimental and individual ones already present. An ambivalence towards the individual seems to be expressed by some formal choices, which made the Stiva da Morts a new landmark in the anthropic fabric.